A network science-based assessment methodology for robust modular system architectures during early conceptual design. (2nd April 2020) - Paparistodimou, Giota; Duffy, Alex; Whitfield, Robert Ian; Knight, Philip; Robb, Malcolm
ABSTRACT: This article describes a methodology to assess, during the early conceptual design stage, the robustness, and modularity of engineering system architectures, which integrates concepts from network science with engineering systems. The application specifically focuses on the architecture of the power, propulsion, and cooling systems of a naval ship. The methodology incorporates a binary Design Structure Matrix as the basis for an assessment of redundancy and modularity effects on robustness, in response to the disruption of modules in the architecture. Robustness is used to drive the module selection, which supports the formulation of a robust module configuration subject to the level of redundancy in the system architecture. The case study results demonstrated that redundancy promotes robustness of the architecture and enables modularity; however, high levels of redundancy in comparison to medium level redundancy does not significantly improve robustness. The novel contribution of this article relates to the combined quantitative assessment of redundancy, modularity and robustness in a collective methodology. This methodology supports conceptual design decision making, allowing early prediction of compliance of requirements that enable cost, development time and survivability targets to be achieved.